Estudio del impacto del envejecimiento en morteros asfálticos (2020)
The objective of this project is to analyze the behavior of asphalt mortars (i.e., mixture of asphalt binder and fine particles with sizes smaller than 1.18mm). The aging process consisted in placing the loss asphalt mortar in an oven at 95oC for 3, 6, 9, 20, 25 and 30 days. The behavior of these mortars was also compared with 3 control mixes made up of: a mix with 100% virgin asphalt binder and virgin aggregates, a mixture of virgen aggregates and long-term aged binder using the pressure vessel (i.e., binder 100% PAV) and, finally, a mixture with 70% virgin asphalt binder and 30% PAV asphalt with virgin aggregates. Finally, an application of this methodology is presented by evaluating the rheological behavior of an asphalt mortar aged 30 days with different doses of a rejuvenator of vegetable origin. The results of this research show that the manufacturing method of the mortar...